Corn Cost-Return Budget in Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on typical corn production practices in northeastern Kansas.
MF571_1998_10
Keywords: MF571; Economics; Crops; MF